Synthesis and some properties of poly-5-vinyl-N,N′-dimethyltetrazolium salts - Voitekhovich, Sergei V.; Grigoriev, Yuri V.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2024)
Poly-5-vinyl-N,N′-dimethyltetrazolium salts, the first representatives of ionic carbochain polymers with a positively charged tetrazole ring in the side chain, were synthesised using polymer-analogous transformations of polyacrylonitrile. The synthesis of salts involves the cycloaddition reaction of sodium azide to polyacrylonitrile to form poly-5-vinyltetrazole, the exhaustive alkylation of which with dimethyl sulfate leads to poly-5-vinyl-N,N′-dimethyltetrazolium methylsulfate. By treating the latter with aqueous solutions of tetrafluoroboric or perchloric acids, poly-5-vinyl-N,N′-dimethyltetrazolium tetrafluoroborate and perchlorate were obtained respectively. The high efficiency of using the resulting polymers for the selective extraction of palladium from model systems containing ions of other heavy and transition metals has been demonstrated.
Keywords: tetrazoles; polymers; palladium; sorption